Penyuluhan Keteramilan Merajut sebagai Upaya Pemberdayaan Ekonomi Ibu Rumah Tangga di RT 005 RW 011 Tiban Lama - Meldra, Delia Meldra; Mardiansyah, Yopy; Razan Muhammad Railis (Jurnal Tiyasadarma, 2026)
Knitting skills counseling is one form of community empowerment aimed at improving creativity and creating opportunities for home-based creative economic activities among housewives. This community service program was conducted in RT 005 RW 011, Tiban Lama Village, Batam City, on March 12, 2026, involving 10–15 housewives as participants. The activity aimed to enhance participants' basic knitting knowledge and skills while introducing the economic potential of knitted products as an alternative home-based business. The methods employed included counseling, demonstrations, guided practice, discussions, and evaluation through observation of participants' products. The results indicated that participants were able to understand basic knitting techniques and produce simple products such as keychains and knitted flowers. Furthermore, the participants showed high enthusiasm throughout the activity and gained a better understanding of the potential of knitted products within the creative economy. This activity is expected to serve as an initial step toward improving the skills and economic independence of housewives through the development of handicraft-based home businesses.